Blockchain-Based Attribute-Based Encryption Algorithm to Secure Access Control in Digital Library Management Systems - Al Nasar, Mohammad Rustom; Al-Tarawni, Musab A. M.; Kharma, Qasem M.; Alqudah, Mashal Kasem; Hakami, Hanadi (Indian Journal of Information Sources and Services, 2025)
Today, if you walk into any university library, you'll notice the shelves of books, the quiet students, and hidden behind the scenes servers full of digital journals and datasets. Keeping track of all these digital resources in large collections is what digital library management systems, or DLMS, are built to do. But with so much information flying around, the big question is how to keep it all secure and make sure only the right people can see the right parts. Old access control methods like password gates and role lists don't always keep up when the number of users, the number of devices, and the variety of data keep growing. This paper shares a new answer. We take the special power of Blockchain and combine it with a nifty tool named Attribute-Based Encryption, or ABE, to make digital library treasures even safer. Blockchain's design, spread across many machines and always writing permanent, untouchable records, lets us store user identities and access rules where no single person can fiddle with them. ABE works by tying access rights to specific user traits. For example, the system sees that someone is a graduate student in bioengineering or a visiting researcher and grants just the right level of access. Because these rules are trait-based, they can shift with the situation, like if a dataset is meant to be opened only in a hospital and not in a campus dorm. With this blend, we obtain a system that manages user access safely and quickly, shrinks the chance of outsiders peeking, and keeps personal data secret. The rest of the paper lays out how we built this system, what each piece of the design looks like, how we put it to work in a live DLMS, and the performance tests that show it can handle the demands of everyday academic life.